Benefits and Risks of Orthodontic Treatment: A Systematic Review - Hamid, Thalca; Triwardhani, Ari; Wardhana, Louis Krisna (Indonesian Journal of Dental Medicine, 2022)
Background: Malocclusion is one of the main problems of oral and dental health, ranked third after caries and periodontal diseases. In Asian population, the percentage of class II and III Angle malocclusion is 21.42% and 5.76% respectively. Thus, orthodontic treatment is still needed by the people. However, not every patient knows the potential risks that orthodontic treatment, and whether the treatment will bring them benefits they want to achieve. Purpose: this study aimed to describe benefits and risks of orthodontic treatment on the patient and operator through scooping review. Review(s): The search of literatures show that orthodontic treatment increases patient's oral health related quality of life, reducing the risk of traumatic dental injuries in children with large overjet, and reducing the incident of muscle tenderness, and myofascial pain. However, orthodontic treatment poses the risk of damage to the teeth, oral and mucosal pain, speech problems, allergic reactions, and orthodontics relapse. Conclusion: Orthodontic treatment can provide benefits to patients' oral health related quality of life, as well as reducing the incidence of temporomandibular disorder and traumatic dental injuries in children with large overjet. But these benefits must outweigh the risks that can occur in the patient such as teeth damage, oral and mucosal pain, speech problems, allergic reactions, and the probability of relapse must also be minimized.